Teaching efficacy of undergraduate PE students; what are the key predictors and what can PE educators learn from this? - Magill, Ceriann; Cronin, Colum; Walsh, Barbara; Polman, Remco; Rudd, James (Frontiers in Education, 2023)
Introduction Teaching efficacy describes the belief in a teacher's ability to promote learning and this belief is an invaluable asset for all teachers. This study examined the contextual influences that predict the teaching efficacy of first-year undergraduate PE students wishing to enter teacher training programs. Method Using a mixed methods study design, 168 PE students completed an online questionnaire and 16 of these participants took part in semi-structured focus groups. The data collection procedures investigated students' perceptions of PE teaching efficacy and examined students' awareness of how their involvement in PE or sports influenced their decision to study PE. Results Teaching experiences and role model influences were the key predictors of students' perceived PE teaching efficacy. Discussions We recommend that higher education PE programs should facilitate theoretically informed reflective learning opportunities to enable students to understand and make sense of the impact of these key predictors. These opportunities will enable students to understand their starting point in PE teaching efficacy and identify the requirements to develop it. The study extends the existing literature by identifying the key predictors of PE teaching efficacy derived from the acculturation experiences of undergraduate PE students.